(untitled) (Bangladesh Journal of Agricultural Research, 2026)
The field experiment was conducted during Kharif seasons of 2021 and 2022 in the research field of Regional Spices Research Centre, Bangladesh Agricultural research Institute (BARI), Gazipur to evaluate the performances of different polythene mulches on weed management efficiency and fruit yield of chilli var. BARI Morich-2. The experiment was laid out in a Randomized Complete Block Design (RCBD) with three replications. The treatments comprised five polythene mulches (30µ thickness), viz. black polythene mulch, transparent polythene mulch, silver on black polythene mulch, blue polythene mulch and unweeded. The two years’ pooled results revealed that almost all the yield and yield contributing parameters were significantly influenced by polythene mulches to produce fruit yield of chilli. The maximum weed control index (94.61%), weed control efficiency (89.2%), fresh red fruit yield (20.3 t ha-1), dry fruit yield (7.8 t ha-1) and seed yield (482.3 kg ha-1) were recorded from silver on black polythene mulch, whereas the minimum fresh red fruit yield (5.6 t ha-1), dry fruit yield (2.3 t ha-1) and seed yield (118.7 kg ha-1) were found in unweeded plot. It may be suggested that silver on black polythene mulch could be effective in weed control and fruit yield as well as seed yield of chilli. Bangladesh J. Agril. Res. 49(1): 29-41, March 2024